‘n Nuwe horison - Verkenning ten opsigte van ‘n sosiale geskiedenis van die Nederduitse Gereformeerde Sending - Saayman, Willem A. (Verbum et ecclesia, 2003)
The author chooses to write a social mission history of the DRC in order to relate important mission events properly to the developing political economy in South Africa. He chooses to follow the nethodology describe especially by Grundlingh and Hobsbawm. He sees mission history and church history as interchangeable, and views Christian history as an important rubric of general human history. He analyses the period 1934-1961 in this article, and starts with the DRC mission policy established in 1935. The author points out a close entwinement of mission policy and political culture, in that "the solution of the native question" formed the central pivot in both mission and political policy. He analyses events around the publication of the Tomlinson Report to illustrate the link between mission policy and political culture (segregation/apartheid). There were also voices of protest against these developments, especially from people with missionary involvement. The author is convinced that there are various important areas for further research (which explains why he subtitled his article: "A reconnaisance in terms of social mission history"). Some of these areas are the relationship between mission and financial ability and the DRC’s late involvement in urban mission. The author concludes with an ambivalent evaluation of DRC mission from a social historical perspective, but stresses that much more research is needed before any conclusive evaluation can be attempted.